Palatability of black soldier fly larvae in valorizing mixed waste coconut endosperm and soybean curd residue into larval lipid and protein sources - Lim, J.-W. (2019)
The black soldier fly larvae (BSFL) have been widely extolled for the application in managing various solid organic wastes. Owing to the saprophagous nature of BSFL, a rapid valorization of solid organic wastes can be accomplished with the simultaneous production of valuable biochemical compounds derived from larval biomass. In the present works, the mixed waste coconut endosperm (w-CE) and soybean curd residue (SC-r) substrates with increasing protein nutritional constituent were administered to BSFL. The correlations between protein from larval feed substrates and nutritional profiles of BSFL biomasses were ultimately unveiled. The protein from larval feed substrates could be increased by increasing of SC-r portion against w-CE. At the w-CE:SC-r ratio of 3:2, the highest larval total weight gained and growth rate were attained; indicating an optimum protein nutritional constituent in mixed organics (12.4) that could enhance the BSFL palatability. Further increment of protein nutritional constituent in mixed organics was found acidifying the residual larval feed substrate progressively, undermining the growth of BSFL. By feeding the BSFL with optimum mixed organics, the maximum accumulations of larval lipid and protein could be achieved. Transesterification of extracted lipid had demonstrated high in monounsaturated fatty acids (73) which was suitable for biodiesel. The BSFL palatability was finally confirmed from the bioconversion viewpoint of mixed organic wastes. Again, achieving the highest bioconversion efficiency of 14 into larval biomass after accounting the metabolic loss of 54. Therefore, a total of 68 of mixed w-CE and SC-r could be successfully bioconverted. Â© 2018 Elsevier Ltd